2019
DOI: 10.1007/s00167-019-05434-1
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage survival of the knee strongly depends on malalignment: a survival analysis from the Osteoarthritis Initiative (OAI)

Abstract: Purpose Progression of osteoarthritis over time is poorly understood. The aim of the current study was to establish a timeline of “cartilage survival rate” per subregion of the knee in relation to mechanical alignment of the lower extremity. The study hypothesized that there are differences in progression of osteoarthritis between varus, valgus and physiologic lower extremity alignment. Methods Based on hip‐knee‐ankle standing radiographs at baseline, 234 knees had physiologic (180° ± 3°, mean 179.7°), 158 kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Studies have investigated potential risk factors for the progression of knee OA. Factors found to be associated with the progression of tibiofemoral OA include frontal plane malalignment on Xrays 29,30 , decreased bone mineral density on DXA 31 , effusion and synovitis 32e34 , mucinous changes in the anterior cruciate ligament (ACL) 35 , bone marrow edema lesions 34 , elevated cartilage T2 relaxation time 34 , trabecular microstructure deterioration 31 , and increased thigh muscle fat 36 on MRI, quadriceps muscle weakness 37 , hip abductor muscle weakness 38 , and knee pain39. Factors found to be associated with the progression of patellofemoral OA include frontal plane malalignment on X-rays 29 , patella alta 40 , tibia tuberosity to trochlear groove distance 41 , superolateral Hoffa's fat fad edema 42 , and meniscus tear and extrusion 43 on MRI, and quadriceps muscle weakness 44 .…”
Section: Prediction Of Knee Oa and Knee Cartilage Lossmentioning
confidence: 99%
“…Studies have investigated potential risk factors for the progression of knee OA. Factors found to be associated with the progression of tibiofemoral OA include frontal plane malalignment on Xrays 29,30 , decreased bone mineral density on DXA 31 , effusion and synovitis 32e34 , mucinous changes in the anterior cruciate ligament (ACL) 35 , bone marrow edema lesions 34 , elevated cartilage T2 relaxation time 34 , trabecular microstructure deterioration 31 , and increased thigh muscle fat 36 on MRI, quadriceps muscle weakness 37 , hip abductor muscle weakness 38 , and knee pain39. Factors found to be associated with the progression of patellofemoral OA include frontal plane malalignment on X-rays 29 , patella alta 40 , tibia tuberosity to trochlear groove distance 41 , superolateral Hoffa's fat fad edema 42 , and meniscus tear and extrusion 43 on MRI, and quadriceps muscle weakness 44 .…”
Section: Prediction Of Knee Oa and Knee Cartilage Lossmentioning
confidence: 99%
“…Articular degeneration and the development of osteoarthritis are associated with a large social and economic burden, and they can cause physical and psychologic disability [31]. Although hip-knee-ankle angle measurements [1, 19] are commonly used to assess alignment abnormalities in the frontal plane [1, 5, 14, 19, 29, 37, 41], little is known regarding the specific effects of limb axis deformities and progression of osteoarthritis. Using Hirschmann et al’s [24, 25] classification system of different knee phenotypes to assess the FMA and TMA, rather than solely relying on hip-knee-ankle angle measurements, we aimed to find the exact association between the various phenotypes and articular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although current evidence relies solely on the hipknee-ankle angle to differentiate among neutral, valgus, and varus knees, recent studies have reported extreme variability in the native knee's alignment [2,8,10,22,24,25,34]. Although abnormal alignment of the limb segments in the frontal plane, among others [1,19], is commonly associated with the progression of knee osteoarthritis [5,14,29,37,41], the exact relationship between limb axis deformities and osteoarthritis remains poorly understood.…”
mentioning
confidence: 99%
“…Stability maneuvers show laxity of the medial ligaments and shortening of the lateral ones, these are essential elements to be taken into account for treatment. [14,15] Radiography is of great help for the diagnosis, but it is important to remember that osteoarthritis is an entity in which the clinical and imaging features are not linear and symmetrical, hence there may be patients with marked degenerative changes on radiographs and have few symptoms or vice versa. On plain radiographs Fujisawa point should be calculated to determinate osteotomy and evaluate limb alignment after surgical procedures.…”
Section: Pertinent Physical Examination and Imagingmentioning
confidence: 99%